Maturing pattern for body size, doe reproductive performance and kid mortality rate of savanna and red kalahari goats - Rosali, Mohamad Hifzan (2015)
The domestic production level of chevon only able to meet 13% of the demand. Savanna and Red Kalahari goats were brought from South Africa to evaluate their potential under Malaysian environment thus, can fulfill the local demand of chevon meat. Growth and reproduction are among the aspects being looked at to determine the economic merits. The objective of this study was to evaluate the performance of Savanna and Red Kalahari goats in terms of mature size, reproductive performance and kid mortality rates under Malaysian conditions. Brody, Gompertz, von Bertalanffy, and Logistics models were used to determine the mature size (A) and maturation rate (k) of Savanna and Red Kalahari does. The goodness of fit of the models was determined by the highest coefficient of determination (R2).The estimated mature weight of Savanna goats as derived from Brody, Gompertz, von Bertalanffy, and Logistic model was 52.57 kg, 52.06 kg, 52.18 kg, and 51.89 kg while for Red Kalahari goats was 52.96 kg, 48.88 kg, 49.81 kg, and 47.24 kg respectively. All the parameters taken fit in the model excellently (R2 above 90%). The best fit model for estimated mature weight of Savanna and Red Kalahari goat were von Bertalanffy Model (94.7%) and Brody Model (97.7%). An estimated asymptote for body length and height at withers derived from Brody, Gompertz, von Bertalanffy, and Logistic models showed that Red Kalahari were longer (P<0.05) and taller (P<0.05) than Savanna goats. The correlation coefficients between the mature size and rate of maturing for their body weight, body length, and height at withers were negative. The conception rate, fertility rate, kidding rate and prolificacy rate of Savanna does were higher compared to Red Kalahari goats (92.4 vs. 90.6, 89.9 vs. 86.8, 137 vs. 125.6 and 152.3 vs. 144.6) but there was no significant difference. Litter size at birth and litter size at weaning was higher for Savanna compared to Red Kalahari goats (1.55 vs.1.49, 1.26 vs. 1.16).There was no significant difference in Savanna and Red Kalahari does with average weaning rate (113 vs. 100) and multiple births (48.6 vs. 40.2) The pre-weaning mortality rate among Red Kalahari kids was higher than Savanna kids (19.7 vs. 17.5%) and it makes the survivality rate of Savanna kids higher (82.5%) compared to Red Kalahari kids (80.3%). Red Kalahari also had a higher post-weaning mortality than Savanna goats (14.3 vs. 13.0%). Considering the overall performance in reproduction and growth, Savanna and Red Kalahari goats had a good potential to meet a demand as a good breeding stock goats in Malaysia. It is recommended that further study using a larger sample and a longer period of time should be done.